Using a fingerprint scanner to protect data in medical information systems - Dovnar, O.I.; Babakov, M.F.; Cherkis, V.I. (Radiotekhnika, 2022)
Since the beginning of hostilities, medical institutions have suffered from cyber attacks, the number of which is not decreasing. The load on the servers even before the start of the war was already quite significant. Since Ukraine suffered severe restrictions due to Covid-19, in part, most institutions were transferred to global medical databases, but with a serious breakthrough, digital capacities did not have time to grow. Even small cyber attacks in the medical field can be critical, so it is necessary to identify accurately medical personnel for access and implement a special application, which will not allow other people to get it, this makes it possible to block immediately all other requests without processing, and this is one of the ways to optimize and increasing security. The task can be solved by standard means of authorization, but they are quite easy to bypass, ordinary software can also be reprogrammed, identification by phone number can be too expensive, so a combined method is proposed: special equipment for reading fingerprints and the corresponding software application. This method is sufficiently reliable and simple to implement (medical personnel will only need to put their finger to the sensor), as well as economical and not demanding. The developed prototype for authorization on the Arduino hardware platform provides the necessary functionality and meets the task. The sensor recognizes more than 100 people, and the convenient mini USB allows you to connect conveniently the device to any computer port. A special algorithm will block the device in case of intervention by a person who does not have access to the corresponding resource. Can be easily reprogrammed and configured to the required equipment, and the case can be printed according to the necessary requirements.